Abundance Trends of Pacific Salmon During a Quarter Century of ESA Protection - Michael J. Ford; Steven T. Lindley; Katie A. Barnas; Andrew O. Shelton; Brian C. Spence; Laurie A. Weitkamp; Damon M. Holzer; David A. Boughton; Elizabeth E. Holmes; James M. Myers; Chris E. Jordan; Heidi Fish; et al. (Fish and Fisheries, 2025)
Between 1989 and 2007, 28 Distinct Population Segments (DPS) of Pacific salmon ( Oncorhynchus spp.) spawning in rivers in California and the Pacific Northwest (Oregon, Washington, Idaho) were listed (protected) under the US Endangered Species Act (ESA). In the roughly 25 years since then, considerable efforts have been made to recover these populations, but no DPS has increased sufficiently to be delisted. We evaluated abundance trends of ESA‐listed Pacific salmon DPS, along with DPS that were not ESA‐listed. Our goal was to evaluate whether protected DPS increased in abundance during the period of protection (nominally 1995–2020 in our study), either in absolute terms or relative to the unprotected DPS. A majority of the protected DPS had increasing abundance trends over this time period, and protected populations had higher median trends than non‐protected populations of the same species. Geographically, populations in the Pacific Northwest had higher median trends than those in California. Among species of protected populations, Chinook salmon ( O. tshawytscha ), chum salmon ( O. keta ) and sockeye salmon ( O. nerka ) had higher median trends than coho salmon ( O. kisutch ) and steelhead (anadromous O. mykiss ). For most DPS (listed and unlisted), trends in harvest rates and hatchery releases were relatively stable during the same time period, whereas trends in indicators related to freshwater and marine climate were generally negative for salmon. Our results suggest that salmon recovery actions may have helped to stabilise and increase protected DPS, but most remain far below their recovery goals.

The effects of environmental factors on the migratory movement patterns of Sacramento River yearling late-fall run Chinook salmon (Oncorhynchus tshawytscha) - Cyril J. Michel; Arnold J. Ammann; Eric D. Chapman; Philip T. Sandstrom; Heidi E. Fish; Michael J. Thomas; Gabriel P. Singer; Steven T. Lindley; A. Peter Klimley; R. Bruce MacFarlane (Environmental Biology of Fishes, 2013)